Hubungan Pengetahuan, Sikap dan Tindakan dengan Pelaksanaan Inisiasi Menyusu Dini (IMD) - Nurlama Siregar; Masnila (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2023)
The implementation of Early Breastfeeding Initiation (IMD) at the Maternity Clinic in the working area of the Tanjung Morawa Health Center, Tanjung Morawa District, Deli Serdang Regency is classified as low. This study aims to determine the relationship between knowledge, attitudes, and actions of health workers, mothers, and families with the implementation of Early Breastfeeding Initiation (IMD) at the Maternity Clinic in the working area of the Tanjung Morawa Health Center, Tanjung Morawa District, Deli Serdang Regency. This type of research is an analytic survey using a cross-sectional approach. The population in this study were all mothers giving birth at the Maternity Clinic in the Working Area of the Tanjung Morawa Health Center with a total of 215 people and a sample of 119 people. Data were obtained using questionnaires and observations, and analyzed by Chi-Square statistical test at α = 5%. The results showed that there was a relationship between knowledge, attitudes, and actions of health workers, mothers, and families with the implementation of early breastfeeding initiation (IMD) at the Maternity Clinic in the working area of the Tanjung Morawa Health Center, Tanjung Morawa District, Deli Serdang Regency. It is suggested that the health workers in charge of assisting deliveries at the Maternity Clinic in the work area of the Tanjung Morawa Health Center, Tanjung Morawa District, Deli Serdang Regency. Need to increase understanding of early breastfeeding initiation and carry out counseling to mothers since the third trimester, especially regarding the implementation of early breastfeeding initiation (IMD).